Facial feedback effect on the sense of body ownership during the rubber hand illusion - Kaneno, Yoshitaka; Ashida, Hiroshi (Frontiers in Human Neuroscience, 2023)
The sense of body ownership, a feeling that one’s body belongs to the self, is an essential aspect of self-consciousness. Studies have focused on emotions and bodily states that could influence multisensory integration for the sense of body ownership. Based on the Facial Feedback Hypothesis, the purpose of this study was to examine whether displaying specific facial expressions affects the rubber hand illusion. We hypothesized that the expression of a smiling face changes the emotional experience and facilitates the formation of a sense of body ownership. In the experiment, participants (n = 30) were asked to hold a wooden chopstick in their mouse to simulate smile, neutral, and disgusted facial expressions during the induction of the rubber hand illusion. The results did not support the hypothesis, showing that proprioceptive drift (an index of illusory experience) was enhanced when the subjects displayed a disgusted facial expression, while the subjective reports of the illusion were not affected. These results, together with the previous studies regarding the effect of positive emotions, suggest that bodily affective information, regardless of its valence, facilitates multisensory integration and could influence the conscious representation of the bodily self.